Stances with Wolves: The Story of Ojibwe Opposition to Wisconsin?s Wolf Hunt and the Proposed Use of Buffer Zones as a Geographic Solution - Wilson, Summer; Swenson, Emily; Jean, Corey (My University, 2013)
Upon its establishment in 2012, the wolf hunt forged a divide between the state of Wisconsin and its sovereign Ojibwe nations. The purpose of this research is to explore the history of cultural, political, and scientific issues that instigated this break from the tradition of cooperative management, as well as addressing the current structure and composition of the decision-making system that continually disregards the Ojibwe. The implementation of buffer zones is ultimately proposed as a geographic compromise to mediate concerns of the wolf's presence in Wisconsin while considering the separate interests of all stakeholders, and the wolf itself.
Includes Maps, Charts, Figures and Bibliography.
Keywords: Buffer Zones; Wisconsin; Wolf hunt; Wolves; Ojibwe